Thermophilic ATP synthase has a decamer c-ring: Indication of noninteger 10:3 H(+)/ATP ratio and permissive elastic coupling - Mitome, Noriyo (National Academy of Sciences, 2004)
In a rotary motor F(o)F(1)-ATP synthase that couples H(+) transport with ATP synthesis/hydrolysis, it is thought that an F(o)c subunit oligomer ring (c-ring) in the membrane rotates as protons pass through F(o) and a 120° rotation produces one ATP at F(1). Despite several structural studies, the copy number of F(o)c subunits in the c-ring has not been determined for any functional F(o)F(1). Here, we have generated and isolated thermophilic Bacillus F(o)F(1), each containing genetically fused 2-mer–14-mer c (c(2)–c(14)). Among them, F(o)F(1) containing c(2), c(5), or c(10) showed ATP-synthesis and other activities. When F(1) was removed, F(o) containing c(10) worked as an H(+) channel but F(o)s containing c(9), c(11) or c(12) did not. Thus, the c-ring of functional F(o)F(1) of this organism is a decamer. The inevitable consequence of this finding is noninteger ratios of rotation step sizes of F(1)/F(o) (120°/36°) and of H(+)/ATP (10:3). This step-mismatch necessitates elastic twisting of the rotor shaft (and/or the side stalk) during rotation and permissive coupling between unit rotations by H(+) transport at F(o) and elementary events in catalysis at F(1).